The effect of temperature and rain on the cultivation of fig production and trees in the province of Kirkuk for the duration (2011 - 2021) (Journal of the College of Basic Education, 2023)
The most important factors affecting agricultural production and the most controlling in determining the amount of agricultural production are natural factors, especially temperature and rain. It aims to study the thermal requirements of the fig tree crop in Kirkuk Governorate and the thermal potential available in the governorate by relying on climatic data for the period (2011-2021) in order to know the extent of the effect of temperature and rain on the cultivation and production of the crop. The research concluded that the study area is a region It is climatically appropriate for the cultivation of the crop, and there is a variation in the average temperatures during the study period, and it was found that the temperature is one of the most important climatic elements affecting the cultivation of fig trees in the study area.